Penerapan Pembelajaran Kooperatif Tipe Nht untuk Meningkatakan Aktivitas dan Hasil Belajar IPA Pokok Bahasan Gaya pada Siswa Kelas IV SD Negeri 41 Mataram - Johariah, Hj. (YASIN, 2022)
The purpose of this study was to increase learning activities and science learning outcomes in fourth grade students at SD Negeri 41 Mataram, given the low level of student learning activities in that class so that their learning outcomes were far below standard. This type of research is descriptive which means that it describes the data obtained through observation, practice questions and learning achievement tests in each cycle. This research was conducted at SD Negeri 41 Mataram learning 2017 / 2018, with the research subjects being class IV students, totaling 14 students. The research instrument used was Student Worksheets, observations of students and teachers. Retrieval of learning outcomes data using an evaluation test instrument of 15 multiple choice questions and observation sheets to calculate student activity. Analysis of learning outcomes data using individual completeness and classical completeness, so that the average achievement of student learning activities in cycle 1 is 73, and for learning outcomes is 79 while in cycle 2 student learning activities is 96 and for student learning outcomes is 93. So that it can be said that cooperative learning of the Numbered Heads together (NHT) type can increase the achievement and learning activities of class IV students at SD Negeri 41 Mataram in the 2017/2018 academic year.